The Discourse of Satire in Indonesia Political Cartoons At Ã¢â‚¬Å“Poliklitik.comÃ¢â‚¬Â - Sulistyowati, Lilis; Hidayat, Didin Nuruddin; Alek, Alek; Nugraha, Dadan (Universitas Negeri Semarang, 2020)
A specific cartoon is commonly used to lead public opinion to a particular phenomenon. It is created to realize or to ask people opinions or thought on political issues. This study analyzed the satire of political cartoons selected in the themes of Ã¢â‚¬Å“ Rancangan Undang-Undang Kitab Undang-Undang Hukum Pidana Ã¢â‚¬Â (RUU KUHP) or The Draft of the Book of Criminal Law relating three articles on human right, livestock, and land in Indonesia in September 2019. This study identified the satirical messages delivered by cartoonists based on the verbal and visual as text analysis, discourse practices analysis on the netizensÃ¢â‚¬â„¢ comments in cartoon column, and sociocultural analysis becoming the backdrop of these political cartoons. This study employed a descriptive qualitative method using a framework by Fairclough (2000). The findings showed that these political cartoons were used to satire the government and the House of Representatives to reject several drafts considered detrimental to society. This research is expected to be a useful input for the community to understand that cartoons can be used to convey social criticism. Also, people will realize that political cartoons are not only just fun for the humour, but also understand the message expressed by cartoonists in their work. For related media, cartoons can be used to convey social criticism by promoting its benefits for all levels of society.